Are Maine Voters Ready for Drug Policy Reform? Findings from a Statewide Survey - Glover, Robert; Sporer, Karyn; Wollard, Aran (Maine Policy Review, 2023)
Maine is in the midst of an unprecedented overdose crisis, which has sparked debate about the appropriate policy response to increasing prevalence of substance use disorder in our communities. This article draws upon a statewide survey to better understand the policy attitudes of Maine voters toward drug policy reform, specifically restructured drug laws, strengthened pathways to recovery, and improved strategies for harm reduction and preventing overdose deaths. Our results suggest that political rhetoric and policy positions rooted in stigmatization and criminalization of those with substance use disorder are increasingly at odds with the perspectives of Maine citizens. Maine’s unique ideological landscape, voters’ rebuke of criminally focused policy approaches in 2022, and the severity with which Mainers have been affected by substance use can be the basis for a bold set of policy reforms.